ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI AUDIT DELAY PADA PERUSAHAAN TELEKOMUNIKASI - Rachman, Dyah Aulia; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to find out what is the factor of firm size, solvability, profitability, profit and loss of the company operation, complexity of company operation, auditor reputation and auditor opinion have influence to the audit delay on telecommunication companies which are listed in indonesia stock exchange (IDX) in 2011-2014 periods. The sample collection method has been done by using purposive sampling. The data collection is secondary data with documentation method. Testing requirements include the testing of multiple regression analysis that begins with classic assumption test. The result of t test shows that in the factor analysis which are including 1 from 7 factors has significant influence to the audit delay, the complexity of the companys operations. The simultaneous test (f test) gives a result that all of the independent variables have significant influence to the audit delay. And the magnitude of the coefficient of determination or R square (R2) = 0.659, which means that all independent variables affect the dependent variable was 65.9% and the remaining 34.1% is influenced by other factors not examined. While the magnitude of the correlation coefficient (R) = 0.812 shows that the correlation between the dependent and independent variables stronger because the value is above 0.5.Keywords: Audit Delay, Firm Size, Complexity of Companyâs Operation, Auditorâs Reputation, Auditorâs Opinion.